Employing of The Socratic Circle as A Method to Engage - Akhmetova, G.Y.; Sciala, M.; Temirgaliev, K.A. (KU Publ., 2022)
The Department of the History of Kazakhstan, housed in the Medical University of Karaganda, continues to implement and practice diverse methods of teaching and learning amongst second-year medical students. We employed varied techniques to equip our students with learning skills to help them succeed in the social sciences and embed those skills while studying medical subject matters. Indeed, today’s information era allows students everywhere to acquire the required materials to learn content independently; however, they need to know how to construct their knowledge by analyzing and systematizing the concepts requisite to their specialty. The design of this study is qualitative, with the results based on students’ experiences of the Socratic circle discussion in their philosophy course spanning fifteen weeks of their studies between January and May 2019. The students’ responses were accumulated in surveys and focus-group discussions. In addition, 135 students submitted reflections after each practicum class and were scrutinized. Hence, this study aims to explore the extent to which students’ engagement in the Socratic circle discussion influenced their deep learning.
Сократтық шеңберді медицина студенттерін терең оқуға тарту әдісі ретінде қолдану
Использование сократического круга в качестве метода вовлечения студентов-медиков в глубинное обучение
Keywords: deep learning; medical students; Socratic Circle; innovative teaching methods; mind mapping; team building; student-centered approach; project works